Frequency of reinforcement as a parameter of conditioned suppression - Lyon, David O. (1963)
Two pigeons were trained on a multiple VI-1; VI-4 min schedule for food reinforcement until a stable differential rate of response was established. Each component of the multiple schedule was in effect for 10 min and was separated from the other by 1 min time out. An Estes-Skinner conditioned suppression procedure was superimposed on each component of the schedule. The relative magnitude of the suppression behavior was measured during its acquisition and extinction, and at CS durations of 100, 200, and 300 sec. The initial magnitude of the suppression behavior was less severe on the VI-1 baseline than on the VI-4, and it extinguished more rapidly on the VI-1. As the relative duration of the CS was increased, the suppression behavior became less severe on both baselines, but the initial differential magnitude in the suppression remained intact.